Personal Practice as an Element of Emancipatory Adult Education - Holtslander, Catherine (Canadian Journal for the Study of Adult Education, 1997)
"Personal practice" is suggested for adult educators involved in emancipatory adult education. The concept is based upon Michael Polanyi's personal knowledge. Personal practice is based on educators' and learners' social and moral relationships with each other. It is contrasted with individualistic adult education that is based upon principles of technical rationalism—objectivity and detachment. Résumé La «pratique personnelle» est recommandée aux andragogues qui exercent la pédagogic de la libération. Ce concept puise son origine dans les écrits de Michael Polanyi sur le savoir personnel. La pratique personnelle définit la relation sociale et morale entre éducateur et apprenant. On peut lui opposer la notion d'éducation «individualisante» inspirée, de principes rationalistes tels que l'objectivité et le désengagement.